Pendidikan dan Kesadaran Beragama sebagai Fondasi Ketahanan Keluarga pada Pasangan Usia Muda di Sukapura - Abdul Kadir (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
This study aims to analyze the influence of education and religious awareness on household resilience among young couples in Sukapura District, Probolinggo Regency. The phenomenon of rampant divorce in this region, which ranked 7th in East Java in the 2022-2025 period, is the main background of this study. The method used was qualitative with a normative-empirical approach. Data were collected through observation, documentation, and in-depth interviews with perpetrators of early marriage, community leaders, and the Religious Affairs Office (KUA). The results indicate that low formal education and minimal religious education are the main driving factors behind underage marriage. Parents often view marriage as a way out of the family's economic burden. However, physical, psychological, and economic unpreparedness lead to fragile household resilience. These findings confirm that religious awareness serves as a crucial bulwark, providing mental maturity in dealing with conflict. Internalizing religious values ​​is key to maintaining household integrity and realizing a harmonious, loving, and compassionate family amidst the challenges of young age.